Modeling of nonlinear absorption of 5,10-a(2)b(2) porphyrins in the nanosecond regime. - BLAU, WERNER; WANG, JING JING; SENGE, MATHIAS (My University, 2013)
The nonlinear absorption (NLA) properties of free base and metalated porphyrins with a unique 5,10- A2B2 substitution pattern were studied with open Z-scan technique at 532 nm in the nanosecond regime over a broad range of input fluence. The NLA responses were found to be dependent on structural features and the solvent used. In most cases the character of the response differed from that typically observed for other porphyrins under similar experimental conditions (i.e., reverse saturable absorption, RSA), suggesting distinct photophysical properties. A series of models was considered in order to understand the NLA responses. Although the character of the responses varied between compounds and solvents it was found that one model fits best all of the recorded responses. Thus, a Published as: Zawadzka, M.; Wang, J.; Blau, W. J.; Senge, M. O. (2013): Modeling of Nonlinear Absorption of 5,10-A2B2 Porphyrins in the Nanosecond Regime. The Journal of Physical Chemisty A 117, 15?26. 2 four-level model with simultaneous two-photon absorption arising from the higher excited state is proposed (1+1+2 photon absorption). KEYWORDS. Nonlinear optics, optical limiting, macrocyclic dyes, tetrapyrrole
PUBLISHED
Keywords: tetrapyrrole; macrocyc lic dyes; optical limiting; Nonlinear optics